Metabolism of aromatics by Trichosporon oleaginosus while remaining oleaginous - Yaguchi, Allison (Microb Cell Fact, 2017)
BACKGROUND: The oleaginous yeast, Trichosporon oleaginosus, has been extensively studied for its ability to metabolize non-conventional feedstocks. These include phenol-containing waste streams, such as distillery wastewater, or streams consisting of non-conventional sugars, such as hydrolyzed biomass and various bagasse. An initial BLAST search suggests this yeast has putative aromatic metabolizing genes. Given the desirability to valorize underutilized feedstocks such as lignin, we investigated the ability of T. oleaginosus to tolerate and metabolize lignin-derived aromatic compounds. RESULTS: Trichosporon oleaginosus can tolerate and metabolize model lignin monoaromatics and associated intermediates within funneling pathways. Growth rates and biomass yield were similar to glucose when grown in 4-hydroxybenzoic acid (pHBA) and resorcinol, but had an increased lag phase when grown in phenol. Oleaginous behavior was observed using resorcinol as a sole carbon source. Fed-batch feeding resulted in lipid accumulation of 69.5% on a dry weight basis. CONCLUSIONS: Though the exact pathway of aromatic metabolism remains to be determined for T. oleaginosus, the results presented in this work motivate use of this organism for lignin valorization and phenolic wastewater bioremediation. Trichosporon oleaginosus is the first yeast shown to be oleaginous while growing on aromatic substrates, and shows great promise as a model industrial microbe for biochemical and biofuel production from depolymerized lignin. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-017-0820-8) contains supplementary material, which is available to authorized users.